'Looking after the survivors': the health of a cohort of long‐term human immunodeficiency virus patients 25 years on. Issue 5 (13th May 2019) - McNeil, Thomas; Rowe, Emily
Abstract: Background: Patients with human immunodeficiency virus (HIV) infection have higher rates of cardiovascular disease, metabolic disorders and malignancy than their uninfected peers. Aim: To survey the health of a South Australian cohort of long‐term HIV patients, who had been diagnosed with HIV prior to the availability of combination antiretroviral therapy. Methods: Data from 88 patients were collected retrospectively across four domains: demographics, HIV history, antiretroviral medication and medical comorbidity. Results: There were high rates of cardiovascular risk factors, in particular active smoking, dyslipidaemia and diabetes mellitus, which translated into a high rate of ischaemic heart disease and cerebrovascular accidents. A large proportion of the patients suffered depression and cognitive impairment. Approximately one‐fifth of the cohort had been diagnosed with a malignancy, with anal cancer being the most prevalent. Many patients had experienced permanent toxicity from antiretroviral therapy. Conclusion: The present study showed high rates of 'non‐HIV morbidity' in a group of long‐term HIV patients in South Australia. Clinicians should aggressively modify cardiovascular risk factors, ensure appropriate immunisations, monitor mental health and consider targeted malignancy screening in these patients. A robust clinical infrastructure and multidisciplinary team is required to facilitate the complex care needs of long‐term HIV patients.